Pengaruh Penambahan Positioning Dan Pursed LipBreathing Pada Terapi Nebulizer Terhadap PenurunanDerajat Sesak Nafas Pasien Penyakit Paru ObstruktifKronis Di BBKPM Surakarta - Purwanignsih, Susi, Isnaini Herawati, SSt. FT, M. Sc (2017)
Background: Chronic Obstructive Pulmonary Disease (COPD) is defined as a disease or lung disorder which provide ventilation disorders such as airflow obstruction that is progressive and not fully reversible and COPD is recognized as a major cause of morbidity and mortality worldwide. Objective: This study aimed to determine the effect of positioning and pursed lip breathing on nebulizer therapy to decrease the degree of shortness of breath in patients with chronic obstructive pulmonary disease in BBKPM Surakarta. Methods: This study included a quantitative study with a kind of Quasi Experimental research design pre test and post test design. Research using primary data by taking data before and after the intervention. Furthermore, 2 comparing the two results is the pre-test and post-test, where the experimental group was given treatment positioning, pursed lip breathing and nebulizers. The sample using purposive sampling method that meets the criteria iknlusi and exclusion. Total sample study of 30 patients with COPD in BBKPM. Results: The data obtained are not normally distributed, statistical test to test the effect of using the Wilcoxon signed ranks test result that the value sig (p) degree of shortness of breath in the treatment group is 0.001 while sig (p) degree of shortness of breath control group of 0,001. Conclusion: Based on these data we can conclude that there is no difference in the effect of positioning and pursed lip breathing on nebulizer therapy to decrease the degree of shortness of breath in patients with chronic obstructive pulmonary disease in BBKPM